Rural Property in an Age of Transnational Migration: Ethnic Divisions in Southeastern Albania - Stahl, Johannes; Sikor, Thomas (Anthropologica, 2022)
In this article we analyze the effects of transnational migration on rural property relations in post-socialist Albania. Our analysis proceeds by comparing changes in property relations regarding agricultural land in three villages inhabited by different ethnic groups. We demonstrate that the immigration laws of neighbouring countries contribute to a differentiation of migration opportunities and thereby property relations along ethnic lines. The migration practices of Vlach, Macedonian and Albanian villagers unravel the legal designations of land rights instituted by land reform, transforming the Albanian country side and differentiating villages. Our findings, therefore, attest to the significance of migration as a transnational social field with strong effects on rural property relations. Migration flows, immigration laws, localities of migrants’ origin and receiving areas constitute each other in scalar transnational dynamics. These dynamics may lead to ethnically differentiated changes in rural property relations if immigration laws employ ethnic markers to define lines of exclusion and inclusion.